Photodegradation of 2, 4, 5, 6-Tetrachloroisophthalonitrile (Chlorothalonil) by Visible and Ultraviolet Light in the Presence of ZnO and TiO2 - Salih, Raad N.; Naman, Salah-Aldin (Science Journal of University of Zakho, 2019)
photocatalytic degradation of fungicides (chlorothalonil) in suspension aqueous solution with semiconductors (tio2, zno) and without semiconductor has been investigated. the influence of different parameters such as light sources, the concentration of fungicides, type of semiconductors and temperature were studied by uv-visible spectrophotometer at 232 and 254 nm. the degradation reaction order spectra of chlorothalonil were determined which first order at 232 nm and second order at 254 nm. in addition, the rate constant, arrhenius factor and energy of activation can be estimated for both peaks. moreover, conductivity of chlorothalonil has been recorded during the photo-degradation and the rate of reaction also has been determined that dependent on product formation.